Studies on the oil yield, antioxidant activities and solubility from the extraction of pithecellobium jiringan jack seeds using supercritical carbon dioxide - Arsad, Nur Husnina (2012)
Studies on the effects of oil yield, antioxidant activities and solubility from the extraction of Pithecellobium Jiringan (Jack) Prain (P.Jiringan) seeds by using supercritical carbon dioxide (SC-CO2) were carried out at temperatures and pressure ranging from 40 oC to 70 oC, and 27.6 MPa to 44.8 MPa, respectively. Two grams of ground P.Jiringan seeds with the particle size of 215 µm and moisture content of 3.5% were used in this study. The extraction process was carried out for 60 minutes. The antioxidant activities of P.Jiringan oil in SC-CO2 were analyzed by using 2, 2-Diphenyl- 1-Picrylhydrazyl (DPPH) method. The study showed that the maximum oil yield was 89.9 mg, at a pressure and temperature of 44.8 MPa and 70 oC, respectively. Moreover, the highest antioxidant activity was 55.4% for scavenging activity at 34.5 MPa and 60 oC. In addition, the dominant factor for oil yield was pressure, while that for antioxidant activity was temperature. In this study, the solubility data of P.Jiringan oil in supercritical CO2 was measured by plotting experimental data of mass of oil extracted against the mass of CO2 used. At constant temperature, the solubility of oil increased as the density of CO2 increased. Meanwhile, at constant pressure, the solubility of oil increased as the temperature increased even though the density of CO2 decreases. The experimental solubility data was correlated with Chrastil model and del Valle-Aguilera model. The solubility was correlated with Chrastil model at average absolute percent deviation (AAPD%) of 0.213% as compared to the del Valle Aguilera model with AAPD% of 0.570%.